1987
DOI: 10.1016/0169-4332(87)90062-6
|View full text |Cite
|
Sign up to set email alerts
|

On the oxide formation on stainless steels AISI 304 and incoloy 800H investigated with XPS

Abstract: The influence of cold work on the initially formed oxide layer on the stainless steels AISI 304 and Incoloy 8OOH has been studied by XPS. Oxidations were performed at pressures of 10-6-10-4Pa and temperatures of 300-800 K. All samples showed a similar oxidation behaviour. The oxidation rates of iron and chromium are of the same order of magnitude at temperatures below 650 K. Subsequent oxidation results in an iron oxide on top of a chromium oxide layer. At temperatures above 650 K the metal surface becomes enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(42 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…All the open literature agreed that oxide layer formed in PWR primary environment has duplex structure while its chemistry and crystal structure remain controversial [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. Even if it is well established that the outer layer is composed of magnetite Fe 3 O 4 , the inner layer composition is reported to be either a fcc phase enriched in chromium [76,77,[90][91][92][93][94][95][96][97][98][99][100][101], or an hexagonal phase (Cr 2 O 3 ) [87,92,93], or even a mixture of both phases [92]. What's more the early stages of oxidation process (1 min to 5 hours) without applying stress was still not investigated since the already published results describe oxides formed after long exposure times (up to 1,000 hours).…”
Section: State Of the Artmentioning
confidence: 99%
“…All the open literature agreed that oxide layer formed in PWR primary environment has duplex structure while its chemistry and crystal structure remain controversial [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. Even if it is well established that the outer layer is composed of magnetite Fe 3 O 4 , the inner layer composition is reported to be either a fcc phase enriched in chromium [76,77,[90][91][92][93][94][95][96][97][98][99][100][101], or an hexagonal phase (Cr 2 O 3 ) [87,92,93], or even a mixture of both phases [92]. What's more the early stages of oxidation process (1 min to 5 hours) without applying stress was still not investigated since the already published results describe oxides formed after long exposure times (up to 1,000 hours).…”
Section: State Of the Artmentioning
confidence: 99%
“…4. We expect mainly a chromium oxide layer, because the diffusion of Cr is faster than Fe at these temperatures [9]. However, we do not have definitive evidence.…”
Section: Discussionmentioning
confidence: 41%
“…6 gives the presumed oxide/metal interface. From XPS data it has been shown that Ni is not involved in the oxidation process and is not oxidized [24]. From this it is concluded that the oxide/metal interface is situated where the Ni reaches its bulk concentration.…”
Section: Composition Of Oxide Layersmentioning
confidence: 85%
“…(1) Fe 3+ is reduced to Fe*+ [24]; (2) preferential sputtering of one of the components may occur; (3) the sputter rate may change gradually from the oxide to the bulk value, whenever the bulk is internally oxidized. The total oxide thickness of fig.…”
Section: Composition Of Oxide Layersmentioning
confidence: 99%